REACH: una reforma ambiciosa reducida a una versión light por la industria química - Vogel, Laurent (Cuadernos de Relaciones Laborales, 2007)
The changes in the market regualtions on chemical products are the legislative development with the highest impact on occupational health since the Framework Directive in 1989. Workers exposure to dangerous chemicals causes more deaths than work accidents, since chemical risks prevention in the working places is cleraly insufficient. One of the contributing factors is the inadequate regulation on production and marketing of chemicals. Chemicals production is at the interface among occupational health, environmet, industrial policies, technological development and scientific research. Practical consequences of every reform surpass the borders of the European Union and will extend during generations. Even when several books could be written on REACH and its history, this paper focuses on the potential impact of REACH on occupational health.